2007
DOI: 10.1149/1.2435708
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Morphology of Hydrogen-Exfoliated InP and Exfoliation Parameters

Abstract: The effect of different heat-treatments during the hydrogen-induced exfoliation of a thin InP layer to control surface roughness was investigated. Hydrogen implantation was carried out by implanting InP with 5 ϫ 10 16 H 2 + /cm 2 at 150 keV. Exfoliation and transfer of the layer to a GaAs substrate occurred at either 150 or 300°C. Exfoliation at 150°C produced smoother surfaces, 2.8 nm, compared to the sample exfoliated at 300°C, 8.5 nm. This change in surface morphology exhibits a much larger impact than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Our previous efforts for InP showed that a ~0.8 μm layer transfer was adequate for subsequent chemical mechanical polishing and resulted in the transfer of a high quality template layer for subsequent fabrication. (5)(6)(7) For the case of GaN, layer transfer in the range of 0.75 -1.3 μm would promote many different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous efforts for InP showed that a ~0.8 μm layer transfer was adequate for subsequent chemical mechanical polishing and resulted in the transfer of a high quality template layer for subsequent fabrication. (5)(6)(7) For the case of GaN, layer transfer in the range of 0.75 -1.3 μm would promote many different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they later showed layer transfer of InP onto GaAs using the abovementioned implantation parameters. 53 It was found that layer transfer at 150°C gave smoother InP surfaces [root-mean-square (rms) roughness 2.8 nm] compared with layer transfer at 300°C (rms roughness 8.5 nm).…”
Section: Gaasmentioning
confidence: 99%
“…In the case of ion-cutting (or Smart CutTM) process based on wafer bonding and hydrogeninduced layer exfoliation, it is common to transfer III-V layers onto Si. The transferred structure is then used as a template for subsequent epitaxial re-growth of device structures [3][4][5]. Due to the rough as-transferred surface and considerable implantation-induced radiation damage near the surface region of transferred structure, a chemical mechanical polishing (CMP) process and/or other surface treatments are required before re-growth.…”
Section: Introductionmentioning
confidence: 99%